The Development of Patient Monitoring System Application: Integrating Design Thinking and QFD Method - Dharmawan, Muhammad Alfian; Mufidah, Ilma; Martini, Sri; Akbar, Mohammad Deni (International Journal of Social Service and Research, 2023)
COVID 19 and other diseases with high risk of transmission lead to hospital occupancy restrictions. On the other hand, the patient’s family needs to know the most recent patient condition. This research aims to design a patient monitoring system. Thus, the patient's family can monitor the patient's condition without visiting the hospital to reduce the transmission risk. The process of designing this monitoring system is carried out using a design thinking approach which consists of an empathy process, define, ideate, prototype, and test. This design thinking approach is combined with the Quality Function Deployment method. This approach was chosen because design thinking can solve problems effectively by understanding user needs and redefining the user experience problems. The result of this research is the patient monitoring system mockup. The mockup usability was tested using usability questionnaire. Respondents who are stakeholders in one of the hospitals agree that the developed patient monitoring system could solve existing problems.